Revitalisasi Nilai – Nilai Holey Narey bagi Persekutuan Orang Sentani di Jemaat GKI Petrus Waena: Revitalization of Values – Holey Narey's Values for the Sentani Fellowship in the GKI Petrus Waena Congregation - Ruhulessin, Cleopatriza (MURAI: Jurnal Papua Teologi Konstekstual, 2025)
The tradition of holey narey as a local heritage in the Sentani people, is believed to be able to protect and care for human life. This tradition was born from the sacred experiences of the Sentani people of a life of solidarity and togetherness experienced by their ancestors. This soldarity and togetherness is manifested through their attitudes and actions that belong to each other and support each other among members of the community. Holey Narey tends to have a higher level of social cohesion due to being a social norm, rooted in the values of local wisdom and being the sui generis of the Waena people in this tradition. These values make the Waena people able to live together and harmoniously in their daily lives. The method used in this study is a qualitative method with empirical research on the cultural values of the holey narey tradition that strengthens the social life of the Waena people. When this tradition is valued and used as the raw material of local theology, it will result in a moral transformation that strengthens the communion between people. That means theology not only builds relationships with God but also relationships with others